Visual communication through performance collaborations - Miettinen, Satu; Sarantou, Melanie (Frontiers in Communication, 2025)
At the intersection of artistic performance, bioart, technology, and visual communication, this article explores how more-than-humans (MTHs) can be visualised, given a voice, and recognised as active collaborators in societal systems. The BioART Laboratory at the University of Lapland conducted a series of textile and digital art studies focussed on fostering shared growth and collaboration between humans and MTHs. This research aimed to investigate how active cooperation between humans and MTHs can be stimulated through visual communication and what roles improvisation, materiality, and digital technologies play in conveying such processes in a post-humanist context. To address these questions, two studies employing arts-based research were drawn from a series of studies conducted in the laboratory between 2021 and 2022. These studies examined the materiality, performative practices, and digital documentation of MTHs, employing photographic layering techniques and biotextiles. The affordances created through collaboration with MTHs for diverse improvisational and performance practices and the use of digital tools and multidimensional approaches were analysed. This analysis established a critical framework grounded in applied learning and self-reflection to better understand the contributions of MTHs to visual communication.